'Against the Law of God, of nature and the secular world': conceptions of sovereignty in early colonial St. Thomas, 1672-1680. Issue 4 (8th August 2021) - Christensen, Rasmus
ABSTRACT: This article examines conceptions of sovereignty in the Danish Caribbean colony of St. Thomas between 1672 and 1680. It focuses on the colony's first governor, Jørgen Iversen, and his struggles to govern the colony on behalf of Denmark's absolutist monarchy and the Danish West India and Guinea Company. Using insights from recent studies of sovereignty and power in colonial societies, the article explores how Iversen organized the colony's legal system as a means of creating legitimate rule and as a way of transferring the sovereignty of the Danish monarch across the Atlantic. By demonstrating that colonization was a profoundly political project, the article challenges existing historiographical interpretations of early colonial rule that have mainly focused on the economics of Danish Atlantic expansion and the allegedly chaotic and unruly nature of St. Thomas's colonial society. More generally, the article provides new insights into the study of sovereignty and authority in the formation of Caribbean colonial societies.